2015
DOI: 10.1021/acs.analchem.5b00971
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Mass Spectrometry Imaging for Depicting Drug Incorporation into Hair

Abstract: In order to investigate the incorporation of drugs into hair, matrix-assisted laser desorption/ionization-time-of-flight tandem mass spectrometry (MS/MS) imaging was performed on the longitudinal sections of single scalp hair shafts sampled from volunteers after a single oral administration of methoxyphenamine (MOP), a noncontrolled analogue of methamphetamine. Hair specimens were collected by plucking out with the roots intact, and these specimens were prepped by an optimized procedure based on freeze-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 23 publications
0
64
1
6
Order By: Relevance
“…Both high spatial resolution and detection sensitivity are required to measure the distributions of drugs in a strand of hair in detail. Kamata et al previously reported 1‐mm segmental analysis using LC–MS/MS and time‐course analysis using MALDI–IMS of methoxyphenamine in a strand of hair, which was sampled with the root intact . Shima et al also performed the combination of LC–MS/MS and MALDI–IMS for measuring the distribution of zolpidem in a strand of hair …”
Section: Introductionmentioning
confidence: 99%
“…Both high spatial resolution and detection sensitivity are required to measure the distributions of drugs in a strand of hair in detail. Kamata et al previously reported 1‐mm segmental analysis using LC–MS/MS and time‐course analysis using MALDI–IMS of methoxyphenamine in a strand of hair, which was sampled with the root intact . Shima et al also performed the combination of LC–MS/MS and MALDI–IMS for measuring the distribution of zolpidem in a strand of hair …”
Section: Introductionmentioning
confidence: 99%
“…The segments representing the time of intake were positive but also in each case one of the neighbouring segments was positive. This observation has been described before and is likely caused either by the different incorporation routes (blood and sweat) into hair but also by the percentage of telogen hair . Moreover, hair sampling can play a crucial role and may affect the distribution pattern of the positive segments.…”
Section: Discussionmentioning
confidence: 55%
“…More elaborate preparation procedures aimed at enhancing the extraction of specific target compounds have recently been reported (46,47 ). The incorporation of compounds into the hair root has been studied over the course of weeks (48 ). Although most analyses are performed on single strands of longitudinally sliced hair simply plucked from the head, a recent investigation used daily shaved beard hair (49 ).…”
Section: Direct Analysismentioning
confidence: 99%